Pengaruh Brand Awareness dan Brand Image terhadap Keputusan Pembelian Produk Mie Instan Indomie: The Influence of Brand Awareness and Brand Image on Purchasing Decisions for Indomie Instant Noodles - Nur Azizhah (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
This study aims to examine the influence of Brand Awareness and Brand Image on consumers’ Purchase Decision of Indomie instant noodles in the Java region. Indomie is one of the most recognized instant noodle brands in Indonesia, with a significant market share. In a competitive market, understanding how much Brand Awareness and Brand Image affect consumer decisions is crucial. This research employs a quantitative approach, using a survey method through questionnaires distributed to 96 respondents selected via Lemeshow Formula. The data were analyzed using multiple linear regression, including tests of validity, reliability, classical assumptions (normality, multicollinearity, and heteroscedasticity), and hypothesis testing through t-test, F-test, and the coefficient of determination. The findings show that both Brand Awareness and Brand Image have a significant influence—both individually and simultaneously—on consumers’ purchase decisions. Brand Awareness has a statistically significant positive impact, while Brand Image also contributes meaningfully to shaping consumer preferences. The coefficient of determination (R²) is 0.662, indicating that 66.2% of the variation in purchase decisions can be explained by the two independent variables. This research provides practical implications for companies to continuously strengthen brand communication strategies and foster emotional connections with consumers to maintain loyalty and increase purchase intention.